2022
DOI: 10.1111/jhn.13117
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the feasibility of implementing the BeWEL lifestyle intervention programme for people at increased risk of colorectal cancer – from research to real life

Abstract: Background: The BeWEL randomised controlled trial (RCT) of weight loss in people with colorectal adenomas demonstrated that a significant proportion of people are interested in lifestyle interventions (49%) and clinically relevant changes in body weight were achieved at 12-month follow-up. The current work aimed to assess the feasibility of the BeWEL programme invitation and delivery in a nonresearch setting to assess whether the original results could be replicated. Methods: The original BeWel programme was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Thus, simplification of recruitment strategies and the documentation provided may help, whereas emphasis on the information that participants must read and understand before taking part may stand in the way of wider participation. However, a problem with recruitment is a longstanding issue in research (Morgan et al, 2021, Preston et al, 2016 and reliance on healthcare professionals was shown as unsustainable (Anderson et al, 2022).…”
Section: Recruitmentmentioning
confidence: 99%
“…Thus, simplification of recruitment strategies and the documentation provided may help, whereas emphasis on the information that participants must read and understand before taking part may stand in the way of wider participation. However, a problem with recruitment is a longstanding issue in research (Morgan et al, 2021, Preston et al, 2016 and reliance on healthcare professionals was shown as unsustainable (Anderson et al, 2022).…”
Section: Recruitmentmentioning
confidence: 99%
“…There is no one size fits all. Studies on early approaches to make lifestyle changes at the time of cancer screening 17 or digital health resources after treatment 18 are essential to help steer services and inform research in ways that are most effective. Providing the right information is not sufficient.…”
mentioning
confidence: 99%